Categorizing a Face and Facing a Category: The Constructive Impacts of Ambiguity and Uncertainty in Racial Categorization. (June 2023) - Levy, Aharon; Nguyen, Christine; Slepian, Michael L.; Gaither, Sarah; Pauker, Kristin; Dovidio, John F.
The past generation has seen a dramatic rise in multiracial populations and a consequent increase in exposure to individuals who challenge monolithic racial categories. We examine and compare two potential outcomes of the multiracial population growth that may impact people's racial categorization experience: (a) exposure to racially ambiguous faces that visually challenge the existing categories, and (b) a category that conceptually challenges existing categories (including "biracial" as an option in addition to the monolithic "Black" and "White" categories). Across four studies ( N = 1, 810), we found that multiple exposures to faces that are racially ambiguous directly lower essentialist views of race. Moreover, we found that when people consider a category that blurs the line between racial categories (i.e., "biracial"), they become less certain in their racial categorization, which is associated with less race essentialism, as well. Importantly, we found that these two effects happen independently from one another and represent two distinct cognitive processes.